De‐Implementing Low‐Value Care in Dentistry: The Case for Choosing Wisely Campaigns. - Arriola‐Pacheco, Fabio; Bomfim, Rafael Aiello; Born, Karen; Lawrence, Herenia P. (Community Dentistry & Oral Epidemiology, 2026)
De‐implementation refers to the practice within implementation science that targets reducing low‐value care; that is practices that have been proven to be outdated, unnecessary, potentially harmful and in some cases not cost‐efficient. Reducing and removing habitual practices, as well as introducing new care, is not easy, as there are multiple provider, patient and system related factors that can hinder these efforts. The Choosing Wisely campaigns have been one of the ways that de‐implementation of low‐value care has been targeted. Choosing Wisely campaigns consist of recommendations that are implemented through specialty‐specific guidance that can be used by providers, patients and the healthcare systems. While Choosing Wisely campaigns have gained widespread traction in medicine, the spread to oral health has been comparatively limited. This commentary explores some of the existing Choosing Wisely campaign recommendations within dentistry and takes a close look at how overprescription, overtreatment, overtesting, and the inclusion and prioritization of care are addressed through these campaigns. Current Choosing Wisely recommendations provide a useful basis that can be utilized to foster a broader movement towards the de‐implementation of low‐value care in dentistry, thereby facilitating substantive changes in oral health practice, policy, and service delivery.